Adapting crowdsourced clinical cancer curation in CIViC to the ClinGen minimum variant level data community‐driven standards. Issue 11 (11th October 2018) - Danos, Arpad M.; Ritter, Deborah I.; Wagner, Alex H.; Krysiak, Kilannin; Sonkin, Dmitriy; Micheel, Christine; McCoy, Matthew; Rao, Shruti; Raca, Gordana; Boca, Simina M.; Roy, Angshumoy; Barnell, Erica K.; et al.
Abstract: Harmonization of cancer variant representation, efficient communication, and free distribution of clinical variant‐associated knowledge are central problems that arise with increased usage of clinical next‐generation sequencing. The Clinical Genome Resource (ClinGen) Somatic Working Group (WG) developed a minimal variant level data (MVLD) representation of cancer variants, and has an ongoing collaboration with Clinical Interpretations of Variants in Cancer (CIViC), an open‐source platform supporting crowdsourced and expert‐moderated cancer variant curation. Harmonization between MVLD and CIViC variant formats was assessed by formal field‐by‐field analysis. Adjustments to the CIViC format were made to harmonize with MVLD and support ClinGen Somatic WG curation activities, including four new features in CIViC: (1) introduction of an assertions feature for clinical variant assessment following the Association of Molecular Pathologists (AMP) guidelines, (2) group‐level curation tracking for organizations, enabling member transparency, and curation effort summaries, (3) introduction of ClinGen Allele Registry IDs to CIViC, and (4) mapping of CIViC assertions into ClinVar submission with automated submissions. A generalizable workflow utilizing MVLD and new CIViC features is outlined for use by ClinGen Somatic WG task teams for curation and submission to ClinVar, and provides a model for promoting harmonization of cancer variant representation and efficient distribution of this information. Abstract : Increasing use of next generation sequencing in cancer generates large volumes of patient variant data for clinical interpretation. Complex intergroup biocuration can help address this problem and includes coordination of group efforts and harmonization of variant formatting. This work describes generation and implementation of such a workflow for collaborative somatic variant curation by ClinGen Somatic Working Groups and the Clinical Interpretation of Variants in Cancer database (CIViC – www.civicdb.org ), along with subsequent automated ClinVar submission.